EFFECT OF SUPPLEMENTAL IRRIGATION ON WHEAT WATER PRODUCTIVITY UNDER RAINFED ECOLOGY OF POTHOHAR, PAKISTAN - ABBAS, SYED HAIDER; BHATTI, ASAF ALI; MUHAMMAD ASIF; ISLAM, ZAFAR; SOHAIL, MUHAMMAD; DIN, RIAZ UD; QAMAR, MAQSOOD; ALI, MURAD; MAJEED, ABID; M. MUNIR (Innovare Journal of Agricultural Sciences, 2015)
For rainfed ecology, water is the most limiting natural resource and its effective utilization is indispensable in order to optimize crop water productivity. A field study on wheat crop was carried out to asses the impact of different irrigation depths through sprinkler irrigation system at three phonological stages viz. tilleing, anthesis and grain filling. Randomized Complete Block Design (RCBD) was used in the trail and had three repeats. Â The area under study received 195 mm seasonal rainfall. Supplemental irrigation depths at three phonological stages, using small quantities of water through sprinkler irrigation system, significantly promoted the crop growth. The irrigation depth 25 mm gave the maximum output for biological yield (6504 ), grain yield (2030 ), thousand grain weight (28), plant height (87 ) and spike length (10 ). The highest water productivity of 0.97 kg/m3 was achieved with 25 mm supplemental irrigation depth when applied at tillering and anthesis stages.